About a graphic representation in Nueva Corónica - Arana Bustamante, Luis Manuel (2015)
This is an analysis of an ilustration of a little kuraka in Guaman Poma de Ayala’s manuscript, the Nueva Corónica y Buen Gobierno. It is made with the end of disentangle the diverse levels of symbolic communication of the picture. The author knew effectively the portraited man and I employed the textual treatment of his figure as an effective comparative help in my study of another Andean kuraka from middle seventeenth century.